2020
DOI: 10.1101/2020.02.16.950998
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Coral reef restoration efforts in Latin American countries and territories

Abstract: 39Coral reefs worldwide are degrading due to climate change, overfishing, pollution, coastal 40 development, bleaching and diseases. In areas where natural recovery is negligible or protection 41 through management interventions insufficient, active restoration becomes critical. The Reef Futures 42 symposium in 2018 brought together over 400 reef restoration experts, businesses, and civil 43 organizations, and galvanized them to save coral reefs through restoration or identify alternative 44 solutions. The sym… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…Studies where motivations were gleaned by surveying restoration practitioners have found primarily biotic, pragmatic or social rationales for restoration, e.g., Bernhardt et al (2007) and Hagger et al (2017). Information on large-scale restoration and in countries where English is not the main language is often not published, with only few exceptions, e.g., Bayraktarov et al (2020), and we may be missing out on more than 35% of the knowledge in conservation if peer-reviewed literature searches are restricted to English (Amano et al, 2016). Another caveat is that funding provided by the research institution in terms of salaries and facilities are rarely acknowledged in a scientific publication.…”
Section: Discussionmentioning
confidence: 99%
“…Studies where motivations were gleaned by surveying restoration practitioners have found primarily biotic, pragmatic or social rationales for restoration, e.g., Bernhardt et al (2007) and Hagger et al (2017). Information on large-scale restoration and in countries where English is not the main language is often not published, with only few exceptions, e.g., Bayraktarov et al (2020), and we may be missing out on more than 35% of the knowledge in conservation if peer-reviewed literature searches are restricted to English (Amano et al, 2016). Another caveat is that funding provided by the research institution in terms of salaries and facilities are rarely acknowledged in a scientific publication.…”
Section: Discussionmentioning
confidence: 99%
“…In response to the loss of coral reefs, organizations around the Caribbean have turned to coral gardening to replenish local populations of coral (Bayraktarov et al, 2020;Young, Schopmeyer & Lirman, 2012). For example, coral restoration projects have resulted in the outplanting of tens of thousands of nursery-reared Acropora corals on Florida reefs each year (Schopmeyer et al, 2017;Lirman & Schopmeyer, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Selection of resilient genotypes could improve restoration efficiency, reduce costs and, ensure that restored populations do not meet the same fate as their predecessors. Although recommended in restoration guidelines (e.g., Baums et al, 2019;Coral Restoration Consortium, 2020), few projects report preselecting genotypes via an assessment of stress resilience before conducting nursery efforts (e.g., Morikawa and Palumbi, 2019; Fundemar and Iberostar case studies in Bayraktarov et al, 2020). Restoration efforts show genotypic driven phenotypic divergence in survivorship and response to thermal stress (Drury et al, 2017;Ladd et al, 2017), yet our understanding of which traits may assure resilience to future climate conditions remains rudimentary.…”
Section: Enhancing Stress Resilience and Reproductive Activitymentioning
confidence: 99%
“…Although some operators facilitate partial public access, few systems are specifically built to cater to a greater audience including non-swimmers or non-divers. However, operators are starting to explore this avenue, as for example the Wave of Change project of the Iberostar Group in Bayahibe, Dominican Republic, which creates an ex situ, land-based, nursery that caters to both, research as well as educational purposes (Bayraktarov et al, 2020). Nevertheless, the outreach, entertainment and educative value to a greater public audience of coastal land-based coral gardens remains vastly unexplored.…”
Section: Land-based Coral Gardens As Blue Economical Assetsmentioning
confidence: 99%
See 1 more Smart Citation